Overexpression of PKD1 Causes Polycystic Kidney Disease - Thivierge, Caroline (American Society for Microbiology, 2006)
The pathogenetic mechanisms underlying autosomal dominant polycystic kidney disease (ADPKD) remain to be elucidated. While there is evidence that Pkd1 gene haploinsufficiency and loss of heterozygosity can cause cyst formation in mice, paradoxically high levels of Pkd1 expression have been detected in the kidneys of ADPKD patients. To determine whether Pkd1 gain of function can be a pathogenetic process, a Pkd1 bacterial artificial chromosome (Pkd1-BAC) was modified by homologous recombination to solely target a sustained Pkd1 expression preferentially to the adult kidney. Several transgenic lines were generated that specifically overexpressed the Pkd1 transgene in the kidneys 2- to 15-fold over Pkd1 endogenous levels. All transgenic mice reproducibly developed tubular and glomerular cysts and renal insufficiency and died of renal failure. This model demonstrates that overexpression of wild-type Pkd1 alone is sufficient to trigger cystogenesis resembling human ADPKD. Our results also uncovered a striking increased renal c-myc expression in mice from all transgenic lines, indicating that c-myc is a critical in vivo downstream effector of Pkd1 molecular pathways. This study not only produced an invaluable and first PKD model to evaluate molecular pathogenesis and therapies but also provides evidence that gain of function could be a pathogenetic mechanism in ADPKD.